2015
DOI: 10.3171/2014.8.jns1459
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of hand coordination and laterality of carotid endarterectomy

Abstract: OBJect Neurocognitive performance is used to assess multiple cognitive domains, including motor coordination, before and after carotid endarterectomy (CEA). Although gross motor strength is impaired with ischemia of large cortical areas or of the internal capsule, the authors hypothesize that patients undergoing CEA demonstrate significant motor deficits of hand coordination contralateral to the operative side, which is more clearly manifest in the nondominant hand than in the dominant hand with ischemia of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Early cognitive dysfunction was associated with a number of different patient characteristics, medications and genetic alleles: age, diabetes mellitus, statin usage, neurovascular anatomy, and certain alleles of ApoE, phosphodiesterase and complement. 712 Of note, we found that statin usage dramatically decreased the incidence of new neurologic findings and eCD after CEA in asymptomatic patients, defined as those patients without a history of previous stroke or transient ischemic attack. This effect was less evident in symptomatic patients.…”
Section: Introductionmentioning
confidence: 78%
“…Early cognitive dysfunction was associated with a number of different patient characteristics, medications and genetic alleles: age, diabetes mellitus, statin usage, neurovascular anatomy, and certain alleles of ApoE, phosphodiesterase and complement. 712 Of note, we found that statin usage dramatically decreased the incidence of new neurologic findings and eCD after CEA in asymptomatic patients, defined as those patients without a history of previous stroke or transient ischemic attack. This effect was less evident in symptomatic patients.…”
Section: Introductionmentioning
confidence: 78%
“…The finding that the region most vulnerable to these lesions was the motor/premotor area (BA 4/6) is consistent with other studies of carotid revascularization. Heyer et al (2015) studied 374 patients undergoing CEA and found that post-procedure changes in hand dexterity were associated with the side of the surgery. Specifically, procedures contralateral to the nondominant hand (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, endovascular procedures are effective means of preventing stroke, and whereas serious associated complications are rare ( Brott, 2010 ), there have been inconsistent studies suggesting these lesions may be linked to subtle post-procedural cognitive decline and increased vulnerability to future cognitive declines ( Aharon-Peretz et al, 2003 ; Fink et al, 2015 ; Ghogawala et al, 2008 ; Heyer et al, 1998 ; Tiemann et al, 2009 ; van Dijk and Kalkman, 2009 ; Wasser et al, 2011 ; Zhou et al, 2017 ; Zhou et al, 2012 ). For example, one large study showed changes in hand dexterity related to side of intervention ( Heyer et al, 2015 ). To identify potentially subtle dysfunction, it is crucial to have highly specific knowledge of which brain systems are affected in order to develop sensitive and focused assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the influence of the laterality of CA revascularization on adverse neurological outcomes are limited (Bossema et al, 2007 ; Baracchini et al, 2012 ; Heyer et al, 2015 ). The study by Bossema et al ( 2007 ) demonstrated that cognitive changes, measured by neuropsychological tests sensitive to hemispheric specialization, are irrespective of the side of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Baracchini et al ( 2012 ) also found no impact of the CEA side on any of the indicators of cognitive performance. Heyer et al ( 2015 ) investigated the relationship between the laterality of CEA and fine hand deficits using the Grooved Pegboard test. The authors demonstrated greater subtle deficits of hand coordination in the non-dominant hand compared to the dominant hand in patients undergoing CEA of the opposite carotid artery.…”
Section: Introductionmentioning
confidence: 99%